PERBEDAAN LAMA LEPAS TALI PUSAT PERAWATAN DENGAN MENGGUNAKAN KASA STERIL DIBANDINGKAN KASA ALKOHOL DI DESA BOWAN KECAMATAN DELANGGU - Utami, Deffy Gita Budi; Sulastri, Sulastri (Jurnal Berita Ilmu Keperawatan, 2010)
Infection still be the main causes of illness and died on neonates. Based on the survey of demography and healthy in Indonesia 2002-2003, the amount of infant die in 2002-2003 is 35 per 1000 lively born, and the amount of neonatus die is 20 per 1000 lively born. Umbilical cord is port de entry of infection that can causes sepsis fastly. The technique to maintenance of that clean is the main principle to prevent sepsis caused umbilical cord infection. Based on study in Bowan Delanggu Region on 2009, neonates birth a year there is 120 infant with the amount fertile age pair there is 326. There is no hospital or community health center, there just a clinic. Infant that was born in clinic have a maintenance care one day only, after that infant can go home. This study aimed to identify the differences of length a part on umbilical cord which use gauze sterile compared with alcohol application in Bowan Delanggu Region. This research using descriptive comparative type and posttest only control group design. The population in this research is all of neonates that approximately born in 27th September until 16th October 2010 amounted 26. This research using total sampling, so the amount of sample is 26 respondents. For equally amount sample if 10 infant with gauze sterile treatment and 10 infant with alcohol application. The statistical analysis used was Mann Whitney statistical test with a confidence value 0,05%, the probability Î± = 0,011. Based on the results of this research note that the value of Mann Whitney test of the differences of length a part on umbilical cord which use gauze sterile compared with alcohol application in Bowan Delanggu Region is less than the value ï² 0,011< 0.05 . Then Ha accepted or Ho rejected. So the conclusion is there is the differences of length a part on umbilical cord which use gauze sterile compare with alcohol application in Bowan Delanggu Region.